PENINGKATAN HASIL BELAJAR SISWA KELAS 2 PADA MATA PELAJARAN MATEMATIKA DENGAN METODE POWER POINT SDN 14 SUKAJADI PEKANBARU - Zetra Hainul Putra; Jesi Alexander Alim; Asmiah Asmiah (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2023)
The role of the teacher as an educator is very important, teachers are required to be able to use a variety of learning media that are affective and interesting foe students when delivering learning materials. Learning media that can make students active is interactive power point media that has been developed. With the use of interactive power point media, it is hoped that is can focus students’ attention more, so that students are more interested when participating in learning. Interactive power point media can also help students be able to master and optimally use their potential and creativity. It is for this reason that researchers conducted research on Improving Mathematics Learning Outcomes About Addition and Subtraction on Currency by Using Power Point Interactive Media For Grade 2 Students of SD Negeri 14 Sukajadi, Pekanbaru City